Nitrogen-rich porous covalent imine network (CIN) material as an efficient catalytic support for C-C coupling reactions - Bhunia, Manas K.; Das, Swapan K.; Pachfule, Pradip; Banerjee, Rahul; Bhaumik, Asim (Dalton Transactions, 2012)
In an effort to expand the realm of possibilities of nitrogen-rich porous materials that could be used in catalysis, herein we report the synthesis of a new highly nitrogen rich (ca. 45%) porous covalent imine network (CIN-1) material employing simple Schiff base chemistry and further grafting its surface with palladium. Pd-loaded CIN-1 support acts as a truly heterogeneous catalyst towards Suzuki C-C coupling reaction between aryl halides with arylboronic acids. High surface area and excellent accessibility of the catalytic sites make it very efficient for heterogeneous catalysis. The stability of the catalyst due to intimate contact between nitrogen-rich organic support and metal allows several reuses with only a minor loss in catalytic activity.

Nanoparticle size-fractionation through self-standing porous covalent organic framework films - Dey, Kaushik; Kunjattu, Shebeeb H.; Chahande, Anurag M.; Banerjee, Rahul (Angewandte Chemie-International Edition, 2020)
Covalent organic frameworks (COFs) have attracted attention due to their ordered pores leading to important industrial applications like storage and separation. Combined with their modular synthesis and pore engineering, COFs could become ideal candidates for nanoseparations. However, the fabrication of these microcrystalline powders as continuous, crack-free, robust films remains a challenge. Herein, we report a simple, slow annealing strategy to construct centimeter-scale COF films (Tp-Azo and Tp-TTA) with micrometer thickness. The as-synthesized films are porous (SA(BET)=2033 m(2) g(-1) for Tp-Azo) and chemically stable. These COFs have distinct size cut-offs (ca. 2.7 and ca. 1.6 nm for Tp-Azo and Tp-TTA, respectively), which allow the size-selective separation of gold nanoparticles. Unlike, other conventional membranes, the durable structure of the COF films allow for excellent recyclability (up to 4 consecutive cycles) and easy recovery of the gold nanoparticles from the solution.
Keywords: covalent organic frameworks; films; nanofilter; Nanoparticles; size-selective separation